Aspects of the social and political history of Langa Township, Cape Town, 1927-1948 - Musemwa, Muchaparara (1993)
Bibliography: pages 198-213.This study focuses on the social and political history of Africans in Langa Township from 1927 to 1948. Langa conveniently and justifiably serves as a good case study of the urban African experience because it is the area in Greater Cape Town, during this period, where there was the largest concentration of a relatively organised, stabilised and permanent African working class community. It is also the oldest township with the deepest roots and longest evolution in Cape Town. Langa also makes an interesting area of study because the politics surrounding its evolution as an urban African segregated residential township presents it not only as an arena of social conflict between the ruler and the ruled, but also stands out as a veritable testimony of the African struggle to become an integral part of the city. The thesis traces what, initially, began as an "externalised" struggle by Africans against the forced removals from the city and Ndabeni Location to Langa and attempts to establish the continuities of this struggle within the township - i.e."internalised" struggle. African popular struggles in Langa predominantly centred around such issues as rents, railway fares, living conditions, restrictions on beer brewing and trading activities, the demand for direct municipal representation and the freedom of movement. The study explores the nature of the relationship that subsisted between the Langa residents and the Cape Town City Council and the internal social and political relations in the Langa community, paying particular attention to conflicting tendencies and the forms of resolution implemented. The thesis aims to highlight the fact that protest and resistance were the only weapons that empowered the Langa residents to fight against unilateral unpopular decisions by the local authority or central government. Flowing from these findings is an attempt to discover how the lived experiences of the Langa people, their frustrations, disillusionment, crises of expectations, translated into political consciousness and how these help us to explain the people's role in nationalist politics. Alternatively, this will help us to explain how political parties, the African National Congress (ANC), the Communist Party of South Africa (CPS A), and the National Liberation League (NLL) exploited the crises in civic matters to enhance or strengthen their support bases and with what results